2011
DOI: 10.1007/s10072-011-0733-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statin and deferoxamine administration on neurological outcomes in a rat model of intracerebral hemorrhage

Abstract: Deferoxamine (DFX), a potent iron-chelating agent, reduces brain edema and neuronal cell injury that develop due to the hemolysis cascade. Statins have neuroprotective effects via anti-inflammatory action and increment of cerebral blood flow after intracerebral hemorrhage (ICH). The purpose of this study was to identify the effects of combined DFX and statins treatment in an experimental ICH rat model. The treatments were: intraperitoneal (i.p.) injection of DFX (group I), combined treatment of i.p. DFX and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A variety of preclinical studies have shown improved functional outcome, reduced peri-hematomal edema, preserved blood brain barrier, promoted synaptogenesis, and decreased inflammatory reaction and perihematomal cell death in experimental ICH in rodents [47][48][49][50][51][52]. One should keep in mind that in most of these studies, very high dosages of statins are used-that is, dosages that go beyond current recommendations, if translated into the human setting.…”
Section: Potential Effects Of Statins On Outcomes After Intracerebralmentioning
confidence: 94%
“…A variety of preclinical studies have shown improved functional outcome, reduced peri-hematomal edema, preserved blood brain barrier, promoted synaptogenesis, and decreased inflammatory reaction and perihematomal cell death in experimental ICH in rodents [47][48][49][50][51][52]. One should keep in mind that in most of these studies, very high dosages of statins are used-that is, dosages that go beyond current recommendations, if translated into the human setting.…”
Section: Potential Effects Of Statins On Outcomes After Intracerebralmentioning
confidence: 94%
“…Iron overload caused by ICH is an important contributor to neurobiological deficits, brain edema, inflammation, neuron apoptosis and brain atrophy. These effects can be reduced with deferoxamine, an iron chelator [38][39][40][41][42][43][44][45] . However, two studies [46,47] have reported that deferoxamine reduces the level of iron, but does not improve outcomes, in a collagenase-induced ICH model.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of granulocyte-colony stimulating factor (G-CSF) and statins further enhance their neuroprotective capacity with less cell apoptosis than with either agents alone (94). Combination of statins and deferoxamine showed a greater effect on PHE and hematoma volume than either agent alone (95). Unlike animal studies, statin use in humans has been linked to increased PHE volume in ICH patients with no effect on CBF (96).…”
Section: Perihemorrhagic Edemamentioning
confidence: 99%